A Note on Negative Electoral Advertising - Subhadip Chakrabarti (University of Bonn, Bonn Graduate School of Economics (BGSE), 2005)
In their seminal paper, Harrington and Hess (1996) discuss a model where candidates differ along two dimensions - ideology which is modeled by the standard Hotelling-Downs formulation and valence factors which encompass traits which all voters agree as desirable. While valence factor is given, the voter perception of a candidate's ideology can be influenced via advertising. In this expository note, we extend the model model to take account of valence as well as ideological advertising but we restrict our attention only to negative advertising. We find that when the available resources are sufficiently small and certain technical conditions are fulfilled, the expected result holds, namely, the candidate with the higher initial valence index will run a relatively personal campaign while the candidate with the lower initial valence index will run an ideological campaign.
Keywords: D72; C72; 330; Negative Advertising; Electoral Contests; Wahlkampf; Wahlverhalten; Theorie